Information and Communication Technologies in Tourism 2021 2021
DOI: 10.1007/978-3-030-65785-7_55
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Visitor Experience in the Time of COVID 19: The Use of AI Robotics in Pembrokeshire Coastal Pathway

Abstract: AI and Robots represent a major innovation opportunity for the tourism sector, and their potential impact and application offer several new opportunities to enhance and develop the visitor experience. Nevertheless, there has been limited academic research on the use of robots, together with a limited number of destinations embracing this technology. Focusing on the Pembrokeshire Coastal Path, this research paper outlines how a multi methodological approach could be utilised to examine the use of AI and robotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous studies [4,5] have confirmed that robots are a potential solution for the hotel industry to combat the pandemic. Therefore, hospitality service industries, such as hotels, need to make changes in their technology and service models in order to cope with the uncertainty of a labor shortage caused by an aging population and the sudden breakout of the pandemic [5].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies [4,5] have confirmed that robots are a potential solution for the hotel industry to combat the pandemic. Therefore, hospitality service industries, such as hotels, need to make changes in their technology and service models in order to cope with the uncertainty of a labor shortage caused by an aging population and the sudden breakout of the pandemic [5].…”
Section: Introductionmentioning
confidence: 84%
“…Ranieri, Guerra, Angione, Di Giacomo and Passafiume [20] pointed out that the elderly still have a good affinity for technology-which indicates that the impact of intelligent technologies, such as robots, on the daily life of the elderly is gradually increasing, and the possibility of its application in the daily life of users is also increasing. The hospitality service industry, such as hotels, needs to change its technology and service models in order to cope with the uncertainty of a labor shortage caused by an aging population and a sudden pandemic [5]. In the face of uncertain global health issues, such as COVID-19, social robotics has emerged as a beneficial way of assisting or potentially replacing humans in providing services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of this has put unprecedented strain on the tourism industry, resulting in a significant drop in revenue and a lack of liquidity (Chuah and Yu 2021). To deal with the uncertainties in the hospitality industry, they need to bring changes in technological platforms, structure, and processes (Minor et al 2021). It is an excellent option to use robots in their services to survive and recover as it will provide contactless and distanced delivery of the products (Mukherjee and Chittipaka 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted by Lee et al (2018) and Seo and Lee (2021) show robots in hotels and restaurants using the TAM model. Studies conducted by Kim et al (2021); Lau (2020); Minor et al (2021); Wang and Wang (2021) showed robots as a possible solution for the hotel industry to fight the COVID-19 pandemic. Previous studies measured the perception of hotel managers towards robots adoption (Ivanov et al 2020;Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%